Evaluasi Hasil Pembelajaran PAI Terhadap Media dan Gaya Belajar - Hakim, Abdul Azizul (khatulistiwa, 2021)
This research aims to understand the relationship between media and learning style with student learning outcomes in the course learning evaluation PAI in College of Sharia Science (ŠTÍS) Harsyi central Lombok Indonesia by using research methods correlational. Results of the research there is a relationship between media and learning and learning styles with the results of the study. Which are the more complete study or media support in the learning process and learning outcomes of students getting better and getting good student learning style then the better learning results anyway